Development Of Smart Islamic Finance: Synergy Of Artificial Intelligence And Sharia Economic Principles - badawi, afif (Al-Muhtarifin: Islamic Banking and Islamic Economic Journal, 2025)
This research explores the integration of Artificial Intelligence (AI) in the Islamic financial system to create an innovative and sharia principle-compliant Smart Islamic Finance. Using qualitative research methods through literature studies and systems analysis, the findings show that AI can revolutionize four main aspects: (1) automated sharia screening, (2) risk management based on sharia maqashid, (3) optimization of zakat distribution, and (4) big data-based product development. The main challenges include the need to develop algorithms based on fiqh muamalah and handling data bias. This paper presents a conceptual framework for AI-sharia integration as well as policy recommendations for regulators.